Mobile money and financial inclusion in Kenya and Tanzania - Long, Edward Porter (Graduate School of Business (GSB), 2023)
Despite great efforts by the public and private sector in recent years to improve financial inclusion throughout Sub-Saharan Africa (SSA), 45.8 million people remain financially excluded in the SADC (Southern African Development Community) alone. Financial inclusion is a critical component of economic growth, and therefore it is an issue that every country should be concerned with. Mobile money has been seen to be one of the most effective methods to improve levels of financial inclusion throughout SSA, helping millions gain access to basic financial services and products over recent years. This study set out to determine the effect of mobile money on financial inclusion in Kenya and Tanzania. Kenya has been seen to be the leader in mobile money which made it the ideal country to compare and contrast with Tanzania, who is behind Kenya in its mobile money adoption and financial inclusion levels. To achieve the objective of the study, a/the multivariate logistic regression technique was employed to estimate cross sectional regression model of roughly 3,000 respondents in both countries. To investigate how mobile money effected financial inclusion, the study sourced data from Financial Inclusion Insights (FII) Tracker Survey data set from 2017. A variety of independent variables related to mobile money ranging from demographics to mobile money behavior variables were chosen to determine what has the greatest impact on improving an individual's chances of being financially included. Evidence from this study shows that phone ownership and using MM are two of the greatest factors that increase the likelihood of a person being financially included in Kenya and Tanzania. Many of the findings in this study go against the current body of research. Most noteworthy, the data on gender disparities in rural financial inclusion were discovered to be the complete opposite of what many studies have stated to be true in SSA. The data clearly showed higher levels of financial inclusion amongst rural women compared to men in 2017. This finding highlighted a need for future gender specific studies on rural financial inclusion. Additionally, this study presented the idea that a new financially included criterion is needed for the younger population. The data from Kenya showed that respondents between the ages of 15 – 34 were at a disadvantage compared to the older population in becoming financially include